Modernity and the Holocaust - Bauman, Zygmunt 1925-2017 (Polity Press, 1992)
Sociology is concerned with modern society, but has never come to terms with one of the most distinctive and horrific aspects of modernity - the Holocaust. The book examines what sociology can teach us about the Holocaust, but more particularly concentrates upon the lessons which the Holocaust has for sociology. Bauman's work demonstrates that the Holocaust has to be understood as deeply involved with the nature of modernity. There is nothing comparable to this work available in the sociological literature.